How perturbative is quantum gravity? - Eichhorn, Astrid; Lippoldt, Stefan; Pawlowski, Jan M.; Reichert, Manuel; Schiffer, Marc (Arxiv, 2018)
We explore asymptotic safety of gravity-matter systems, discovering indications for a near-perturbative nature of these systems in the ultraviolet. Our results are based on the dynamical emergence of effective universality at the asymptotically safe fixed point. Our findings support the conjecture that an asymptotically safe completion of the Standard Model with gravity could be realized in a near-perturbative setting.